Estudo taxonômico de Humiriaceae no Parque Nacional do Viruá e biologia reprodutiva de duas variedades de Humiria balsamifera aubl. - Holanda, Ana Sofia Sousa de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The Viruá National Park (PNV) in the south of Roraima state, lies in an area predicted to have high botanical diversity. It has recently been the subject of a series of taxonomic and ecological. The present study, conducted between July 2011 and December 2012 consists of a taxonomic treatment of the species of Humiriaceae present in the area, and a study on the reproductive biology of two varieties of the complex Humiria balsamifera. In PNV, Humiraceae is represented by three species: Humiria balsamifera with two varieties, Sacoglottis guianensis also with two varieties, and Schistostemon macrophyllum. Three taxa were not previously recorded from Roraima, The taxonomic treatment includes descriptions, identification keys, photographic plates, and information on the geographical distribution of species in the PNV and other locations. Humiria balsamifera var. guianensis and Humiria balsamifera var. balsamifera f. attenuata have significant morphological differences. They have extended flowering throughout the year, with a peak in august. The bees Trigona spp. Were found to be the main pollinators. Both varieties are self-incompatible and xenogamous. However, they are cross-compatible, thus different varieties may interbreed. The phenological overlap, sharing pollinators and potential interbreeding indicate that pre-zygotic barriers are not effective in reproductive isolation between the varieties. Post-zygotic barriers that allow these varieties can coexist in sympatry.
Keywords: Humiriaceae; Humiria balsamifera; Biologia reprodutiva